"It's Hard, but We Could Kind of Laugh About It": Exploring the Role of Humor in Brain Cancer Caregiving. (April 2022) - Heinsch, Milena; Cootes, Hannah; Wells, Hannah; Tickner, Campbell; Sampson, Dara; Kay-Lambkin, Frances
Research exploring the benefits of humor for caregivers is limited and, to date, no qualitative studies have explored the role of humor in brain cancer caregiving. To address this gap, we analyzed transcripts from twenty-one in-depth telephone interviews conducted with brain cancer caregivers from a strengths perspective. Thematic analysis using Braun and Clarke's method revealed that humor functions as (1) an innate element of the self and relationship, (2) an expression of mutual connection and understanding, (3) a way of managing difficult or awkward moments, (4) a form of avoidance or a welcome distraction, and may be (5) helpful, or unhelpful, depending on where someone is in the brain cancer trajectory. Findings suggest that humor represents an important yet complex individual and family strength for health service providers to identify and build upon.